2019
DOI: 10.1590/1414-431x20198833
|View full text |Cite
|
Sign up to set email alerts
|

Higher values of triglycerides:HDL-cholesterol ratio hallmark disease severity in children and adolescents with sickle cell anemia

Abstract: Dyslipidemia has been described in sickle cell anemia (SCA) but its association with increased disease severity is unknown. Here, we examined 55 children and adolescents with SCA as well as 41 healthy controls to test the association between the lipid profiles in peripheral blood and markers of hemolysis, inflammation, endothelial function, and SCA-related clinical outcomes. SCA patients exhibited lower levels of total cholesterol (P<0.001), low-density lipoprotein cholesterol (LDL-c) (P<0.001), and high-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Our findings stand in agreement with other studies that also reported decreased total cholesterol, HDL-C, and LDL-C levels among SCA individuals in comparison to HbAA individuals [ 19 , 20 , 25 , 27 ]. It is thought that the hypocholesterolemia seen in SCA results from the augmented cholesterol utilization in erythropoiesis consequent to anemia and hemolysis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings stand in agreement with other studies that also reported decreased total cholesterol, HDL-C, and LDL-C levels among SCA individuals in comparison to HbAA individuals [ 19 , 20 , 25 , 27 ]. It is thought that the hypocholesterolemia seen in SCA results from the augmented cholesterol utilization in erythropoiesis consequent to anemia and hemolysis.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the occurrence of hypocholesterolemia in patients with nonhemolytic anemia suggests increased erythropoietic activity [ 17 ]. Moreover, it is also relevant to point that our investigation was carried out in a pediatric population of SCA patients, which could explain some discrepancies with data in the literatures, such as lack of association with different clinical manifestations; however, many of our results are in accordance with previous publications involving patients of a similar age, as well as adults [ 19 , 20 , 25 ]. The cross-sectional design of our study made it difficult to establish any causative roles for lipid parameters with regard to clinical manifestations in SCA, yet the relevant associations found herein will be useful in guiding further evaluations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Hypocholesterolemia in SCD patients has been reported in many SCD cohort studies worldwide, yet the mechanism, pathophysiological manifestations, and association with mortality rate of these altered lipid levels have yet to be 3 BioMed Research International clarified [26][27][28]. Additionally, Song et al have found that the cholesterol level has a U-shaped relation with mortality among Korean adult males and the probability of mortality is increased in patients with cholesterol levels below 135 mg/dL compared to those with cholesterol level between 135 and 200 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglyceride levels were determined using an A25 chemistry analyzer (Biosystems S.A, Barcelona, Catalunya, Spain), while LDL-C and VLDL-C levels were determined by the Friedewald equation [ 26 ]. TC/HDL-C, LDL-C/HDL-C, and triglyceride/HDL-C ratios were calculated to evaluate cardiovascular risk [ 27 31 ]. In addition, non-HDL-C was calculated by TC–HDL-C [ 32 ].…”
Section: Methodsmentioning
confidence: 99%